Conversion as a Turning from the Cave–Labyrinth to the Vision of Totality: Education and Formation in Patočka Based on the Reading of Plato and Comenius - Duque Cano, Santiago Andrés (2026)
This study aims to raise the question of the point of departure and the point of arrival of the movement involved in conversion, drawing on Patočka’s reading of Plato and Comenius. The point of departure is represented through the images of the cave and the labyrinth; the point of arrival is associated with a vision of totality and truth, thanks to which, in Platonic terms, the light of a spark may suddenly ignite and bring about a turning of the gaze toward unity and truth. Through a hermeneutic engagement with Patočka’s texts—one that also appeals to the phenomenological conceptual framework characteristic of this author—the article seeks to highlight the idea of education and formation as conversionand to outline certain conditions of possibility that could foster such a turning of the gaze. Central to thinking through these conditions will be the Platonic concept of chorismós and the general interpretive approach Patočka develops under the heading of negative Platonism. Rethinking education and formation as conversion, drawing on these classical thinkers of the philosophical and pedagogical tradition, may contribute to renewing meanings and problematizations that have fallen into dormancy under the logic of technified performance that has come to dominate schooling.